The Surge in Divorce Rate in Southeast Aceh: An Analysis of Key Factors and the Role of Social Media - Nur Mala Sari; Rahimah Embong (Islamic Studies and Civilization Journal, 2026)
The rising divorce rate in Southeast Aceh Regency in recent years reflects social challenges that require comprehensive analysis. Data from the Kutacane Syar'iyah Court indicates that the number of divorce cases in 2025 has exceeded the total cases recorded in the previous year, highlighting increasing vulnerability within family institutions. This study aims to examine the primary factors contributing to the surge in divorce rates in Southeast Aceh and to analyse the role of social media in shaping marital conflict dynamics. The research adopts a qualitative approach using literature review and secondary data analysis derived from religious court decisions, official judicial reports, and relevant scholarly sources. The findings reveal that economic hardship, lack of spousal responsibility, criminal-related issues, and weak interpersonal communication are dominant factors leading to divorce. Additionally, social media contributes to the escalation of marital conflict by reducing direct communication and increasing the potential for interpersonal tension. These results suggest that social media is not the sole cause of divorce but functions as a supporting factor that accelerates the emergence of domestic conflict. In conclusion, reducing divorce rates requires integrated efforts through strengthening family resilience, enhancing digital literacy, and increasing the involvement of social and religious institutions in family guidance and counselling.